Positive electrode aerogel material, positive electrode, capacitor and preparation method of positive electrode aerogel material
By stirring, foaming and freezing the dispersion of LiCo1/3Ni1/3Mn1/3O2, carbon nanotubes and graphene oxide, a high energy density and power density positive electrode aerogel material was prepared, and the existing positive electrode was solved The complex material process and poor environmental protection problems have achieved efficient supercapacitors.
Patent Information
- Application Number
- CN202411485752.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-27
AI Technical Summary
During the preparation process, the existing cathode materials have complex processes, poor environmental protection, and low power density, making it difficult to meet the needs of high energy density and power density.
The dispersion is formed by LiCo1/3Ni1/3Mn1/3O2, carbon nanotubes, graphene oxide, animal protein foaming agent and water raw materials. After stirring and foaming, insulation and freezing, a positive electrode air condensation that is easy to compound with the current collector is obtained. glue material, and no adhesive is required.
The energy density and power density of the cathode material are improved, the preparation process is simplified, the environmental protection is enhanced, and supercapacitors with high energy density and power density are realized.
Smart Images

Figure BDA0005098667900000091 
Figure BDA0005098667900000101 
Figure BDA0005098667900000111
Abstract
Description
Technical Field
[0001] The invention relates to a positive electrode aerogel material, a positive electrode, a capacitor and a preparation method thereof. Background Art
[0002] A supercapacitor is a charging and discharging device with high power density, long cycle charge and discharge life, high charge and discharge efficiency and good safety, and can be used as a mobile charging facility.
[0003] CN109817467A discloses a method for preparing a composite positive electrode material, wherein a lithium-containing active substance and a surfactant are heated and mixed in water, activated carbon is then added, the mixture is continued, the surfactant is removed by solid-liquid separation, the obtained solid is heat-treated, and the carbon-based composite positive electrode material is obtained after cooling. The positive electrode material needs to be slurried with conductive carbon black, solvent, binder, etc. and coated on a current collector, which has a relatively complicated process, poor environmental protection, and low power density.
[0004] CN115083789A discloses a method for preparing a CNF / zinc-cobalt-nickel oxide / graphene aerogel electrode, comprising mixing zinc salt, nickel salt, cobalt salt, CTAB and NH4F to obtain a mixed solution; mixing the mixed solution with a graphene oxide solution, and then reacting, washing and drying to obtain zinc-nickel-cobalt oxide / rGO; mixing zinc-nickel-cobalt oxide / rGO with deionized water to obtain a zinc-nickel-cobalt oxide / rGO solution; mixing the zinc-nickel-cobalt oxide / rGO solution, carbon black and a CNF solution, and then drying to obtain an aerogel electrode. The energy density and power density of the electrode are low.
[0005] CN106910647A discloses a method for preparing a graphene aerogel composite nickel cobalt oxide nanowire array material, wherein a graphene oxide solution is placed in a reactor, subjected to hydrothermal reaction, cooled naturally, and freeze-dried to obtain a graphene aerogel; nickel chloride hexahydrate, cobalt chloride hexahydrate, and urea are dissolved in deionized water, stirred, and ultrasonically dispersed to obtain a mixed solution; the graphene aerogel is placed in the mixed solution, subjected to hydrothermal reaction, cooled naturally, washed, and freeze-dried to obtain a precursor; the precursor is heated in a tubular atmosphere furnace, and cooled to obtain a graphene aerogel composite nickel cobalt oxide nanowire array material. The material is used as an electrode material, and the energy density and power density of the electrode are low. Summary of the invention
[0006] In view of this, an object of the present invention is to provide a method for preparing a positive aerogel material, and the positive aerogel material obtained by the preparation method has a high energy density and power density. Furthermore, the positive aerogel material obtained by the preparation method is easy to be compounded with a current collector without the use of a binder. Another object of the present invention is to provide a positive aerogel material. Another object of the present invention is to provide a positive electrode. Another object of the present invention is to provide a method for preparing a positive electrode. Another object of the present invention is to provide a supercapacitor. The supercapacitor has a high energy density and power density.
[0007] The above object is achieved through the following scheme.
[0008] In one aspect, the present invention provides a method for preparing a positive electrode aerogel material, comprising the following steps:
[0009] Containing 3.5 to 20 parts by weight of LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, 0.2-1 parts by weight of carbon nanotubes, 0.2-0.8 parts by weight of graphene oxide, a reducing agent, 0.1-0.4 parts by weight of an animal protein foaming agent and water are formed into a dispersion, stirred and foamed to obtain a foam;
[0010] The foam is kept warm at 70-120° C. to obtain a wet gel; the wet gel is frozen to obtain a positive electrode aerogel material.
[0011] According to the preparation method of the present invention, preferably, the insulation time is 3 to 9 hours and the freezing temperature is -30 to -5°C.
[0012] According to the preparation method of the present invention, preferably, the amount of the reducing agent is 0.2 to 2 parts by weight, and the reducing agent is ascorbate; in the dispersion, the concentration of graphene oxide is 3 to 9 mg / mL.
[0013] According to the preparation method of the present invention, preferably, the following steps are further included: washing and drying the dried gel obtained after freezing; and pressing it into sheets under the condition of 5 to 20 MPa to obtain a positive electrode aerogel material.
[0014] On the other hand, the present invention provides a positive electrode aerogel material, which is prepared by the above-mentioned preparation method.
[0015] In another aspect, the present invention provides a positive electrode, comprising a positive electrode current collector layer and a positive electrode active material layer formed of the positive electrode aerogel material, wherein the positive electrode active material layer is attached to the surface of the positive electrode current collector layer.
[0016] In another aspect, the present invention provides a method for preparing a positive electrode, comprising the following steps: laminating a positive electrode aerogel material and a current collector, and then pressing to obtain a positive electrode.
[0017] In yet another aspect, the present invention provides a supercapacitor comprising the above-mentioned positive electrode.
[0018] According to the supercapacitor of the present invention, preferably, the supercapacitor further comprises a negative electrode and an electrolyte;
[0019] The negative electrode comprises a negative electrode current collector layer and a negative electrode active material layer, wherein the negative electrode active material layer is attached to the surface of the negative electrode current collector layer, and the negative electrode active material layer comprises hard carbon, graphite and carbon nanotubes in a mass ratio of (5-15):(1-10):1;
[0020] The electrolyte comprises an electrolyte and a solvent, wherein the electrolyte is LiBF4, and the solvent is propylene carbonate and dimethyl carbonate in a mass ratio of 1:(0.5-3); the concentration of the electrolyte is 0.5-3 mol / L.
[0021] According to the supercapacitor of the present invention, preferably, the supercapacitor comprises a packaging shell, a battery cell and an electrolyte; the battery cell and the electrolyte are located in the packaging shell; the battery cell comprises a positive electrode, a separator and a negative electrode, and the separator is a polyethylene microporous film.
[0022] The positive electrode aerogel material of the present invention has high energy density and power density. Furthermore, the positive electrode aerogel material obtained by the preparation method is easy to be compounded with the current collector without the use of a binder. The positive electrode of the present invention does not need to use organic reagents such as a binder during the preparation process, and can be compounded with the current collector by pressing, thereby improving the energy density and power density and being more environmentally friendly. The supercapacitor of the present invention has both high energy density and high power density. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0024] <Positive electrode aerogel material and preparation method thereof>
[0025] The preparation method of the positive electrode aerogel material of the present invention comprises the following steps: 1 / 3 Ni 1 / 3 Mn 1 / 3 The raw materials of O2, carbon nanotubes, graphene oxide, reducing agent, animal protein foaming agent and water form a dispersion, stir and foam to obtain a foam; keep the foam at 70-120°C to obtain a wet gel; freeze the wet gel to obtain a positive electrode aerogel material.
[0026] Preferably, the raw material is LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 It is composed of O2, carbon nanotubes, graphene oxide, reducing agent, animal protein foaming agent and water.
[0027] LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 The amount of O2 is 3.5 to 20 parts by weight; preferably 5 to 15 parts by weight. 1 / 3 Ni 1 / 3 Mn 1 / 3 The amount of O2 used is 7 to 13 parts by weight.
[0028] The amount of carbon nanotubes used is 0.2 to 1 part by weight, preferably 0.3 to 0.9 part by weight, and more preferably 0.4 to 0.5 part by weight.
[0029] The diameter of the carbon nanotube may be ≤15 nm and the length of the carbon nanotube may be 5 to 15 μm.
[0030] The amount of graphene oxide used is 0.2 to 0.8 parts by weight, preferably 0.3 to 0.7 parts by weight, and more preferably 0.4 to 0.5 parts by weight.
[0031] The oxygen-carbon molar ratio of graphene oxide may be 0.45 to 0.65. The sheet diameter of graphene oxide may be 15 to 50 μm. The sheet thickness of graphene oxide may be ≤10 nm.
[0032] LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 When the amounts of O2, carbon nanotubes and graphene oxide are controlled within the above ranges, the capacitor can have higher energy density and power density.
[0033] The amount of animal protein foaming agent is 0.1 to 0.4 parts by weight; preferably 0.2 to 0.3 parts by weight; more preferably 0.25 to 0.3 parts by weight. The animal protein foaming agent is preferably one or a combination of hydrolyzed animal hoof keratin foaming agent, hydrolyzed animal hair protein foaming agent, hydrolyzed blood collagen foaming agent, and composite animal protein foaming agent. Preferably, the animal protein foaming agent is FP-50A animal protein foaming agent. This can make the aerogel material have an appropriate pore structure, improve the energy density and power density, improve the viscosity of the positive electrode aerogel material, and facilitate fixation with the current collector.
[0034] The amount of the reducing agent can be 0.2 to 2 parts by weight, preferably 0.5 to 1.5 parts by weight, and more preferably 1 to 1.2 parts by weight. The reducing agent is preferably an ascorbate, and more preferably sodium ascorbate. This can fully reduce the energy density and power density.
[0035] In the dispersion, the concentration of graphene oxide is 3 to 9 mg / mL; preferably 4 to 7 mg / mL; more preferably 5 to 6 mg / mL. 1 / 3 Ni 1 / 3 Mn 1 / 3 O2 and carbon nanotubes are evenly dispersed on the graphene oxide skeleton, improving energy density and power density.
[0036] In certain embodiments, LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2 and carbon nanotubes are added into graphene oxide aqueous dispersion and dispersed evenly by ultrasonication; then a reducing agent and an animal protein foaming agent are added.
[0037] The dispersion is stirred and foamed at a rotation speed of 5000 to 20000 rpm; preferably, at a rotation speed of 9000 to 16000 rpm.
[0038] The holding temperature is 70-120° C., preferably 80-110° C., and more preferably 90-100° C. The holding time can be 3-9 hours, preferably 4-8 hours, and more preferably 5-7 hours. This can not only fully reduce the graphene oxide, but also help form a wet gel.
[0039] The freezing temperature can be -30 to -5°C, preferably -25 to -10°C, and more preferably -20 to -15°C. The freezing time can be 3 to 20 hours, preferably 5 to 15 hours, and more preferably 8 to 12 hours. In this way, the wet gel can be fully dried without affecting the pore structure of the product.
[0040] In some embodiments, the method further comprises the following steps: washing and drying the dried gel obtained after freezing; and pressing the dried gel into sheets under a pressure of 5 to 20 MPa to obtain a positive electrode aerogel material.
[0041] Preferably, the washed dried gel is cut off from its upper and lower surfaces before pressing.
[0042] The pressing pressure is 5 to 20 MPa, preferably 8 to 15 MPa, and more preferably 10 to 12 MPa.
[0043] The positive electrode aerogel material of the present invention is prepared by the above method.
[0044] <Positive electrode and preparation method thereof>
[0045] The positive electrode of the present invention comprises a positive electrode current collector layer and a positive electrode active material layer. The positive electrode active material layer is attached to the surface of the positive electrode current collector layer.
[0046] The positive electrode current collector layer may be formed of an aluminum mesh or an aluminum foil. According to one embodiment of the present invention, the positive electrode current collector layer is formed of an aluminum mesh.
[0047] The thickness of the positive electrode current collector layer may be 8 to 16 μm, preferably 9 to 13 μm. In some embodiments, the thickness of the positive electrode current collector layer is 10 to 12 μm.
[0048] The positive electrode active material layer is formed of the positive electrode aerogel material. The thickness of the positive electrode active material layer may be 40 to 130 μm, preferably 50 to 110 μm. In some embodiments, the thickness of the positive electrode active material layer is 65 to 95 μm.
[0049] The preparation method of the positive electrode of the present invention comprises the following steps: laminating the positive electrode aerogel material with the positive electrode current collector, and then pressing to obtain the positive electrode. The positive electrode aerogel material of the invention can be attached to the surface of the positive electrode current collector by physical pressing, without using a binder, a solvent, etc., thereby reducing the introduction of impurity elements and improving energy density and power density.
[0050] The pressing pressure may be 15 to 25 MPa, preferably 17 to 22 MPa.
[0051] <Supercapacitor and its preparation method>
[0052] The supercapacitor of the present invention includes the positive electrode as described above, and may also include a negative electrode and an electrolyte.
[0053] The negative electrode includes a negative electrode current collector layer and a negative electrode active material layer. Preferably, the negative electrode is composed of a negative electrode current collector layer and a negative electrode active material layer. The negative electrode active material layer is attached to the surface of the negative electrode current collector layer.
[0054] The negative electrode current collector layer may be formed of a copper mesh or a copper foil. According to one embodiment of the present invention, the negative electrode current collector layer is formed of a copper mesh.
[0055] The thickness of the negative electrode current collector layer may be 6 to 12 μm, preferably 6 to 10 μm. In some embodiments, the thickness of the negative electrode current collector layer is 6 to 8 μm.
[0056] The negative electrode active material layer includes hard carbon, graphite and carbon nanotubes in a mass ratio of (5-15):(1-10):1. Preferably, the mass ratio of hard carbon, graphite and carbon nanotubes is (8-13):(2-8):1; more preferably, the mass ratio of hard carbon, graphite and carbon nanotubes is (10-11):(5-6):1.
[0057] The thickness of the negative electrode active material layer may be 40 to 130 μm, preferably 50 to 110 μm. In some embodiments, the thickness of the negative electrode active material layer is 65 to 95 μm.
[0058] The electrolyte includes an electrolyte and a solvent. The electrolyte may be LiBF4. The concentration of the electrolyte may be 0.5 to 3 mol / L, preferably 0.8 to 2 mol / L, and more preferably 1 to 1.5 mol / L.
[0059] The solvent is propylene carbonate and dimethyl carbonate. The mass ratio of propylene carbonate to dimethyl carbonate can be 1:(0.5-3), preferably 1:(0.8-2), and more preferably 1:(1-1.5).
[0060] The supercapacitor of the present invention comprises a packaging shell, a battery core and an electrolyte. The battery core and the electrolyte are located in the packaging shell. The composition of the electrolyte is as described above and will not be repeated here.
[0061] The encapsulation shell can be a flexible shell. In some embodiments, the encapsulation shell is an aluminum-plastic film encapsulation shell. The encapsulation shell can also be a steel shell or an aluminum shell.
[0062] The battery cell includes a positive electrode, a separator and a negative electrode. The positive electrode and the negative electrode are as described above and will not be described again. The separator can be a polyethylene microporous membrane.
[0063] The battery cell may be provided with a tab.
[0064] The method for preparing a supercapacitor of the present invention includes an assembly step. In some embodiments, it also includes a step of preparing a positive electrode and / or a step of preparing a negative electrode. The step of preparing the positive electrode is as described above and will not be repeated here. The assembly step and the step of preparing the negative electrode are introduced separately below.
[0065] Assembly steps
[0066] The positive electrode, the separator and the negative electrode are stacked to form a battery cell, the pole ears are welded on the battery cell, and then the battery cell is encapsulated with a packaging shell; the electrolyte is injected into the packaging shell to obtain a supercapacitor.
[0067] Steps for preparing the negative electrode
[0068] Hard carbon, graphite, carbon nanotubes and polyvinylidene fluoride are uniformly mixed, and then slurried with N-methyl-2-pyrrolidone to obtain a slurry. The slurry is coated on the negative electrode current collector, and then dried, rolled, cut into pieces, and vacuum dried to prepare a negative electrode. The amounts of hard carbon, graphite and carbon nanotubes are as described above and will not be repeated here.
[0069] The mass ratio of carbon nanotubes to polyvinylidene fluoride may be 1:(0.5-3); preferably 1:(0.8-2); more preferably 1:(1-1.5).
[0070] The negative electrode current collector may be a copper foil or a copper mesh. According to one embodiment of the present invention, the negative electrode current collector is a copper mesh.
[0071] Here are the raw materials:
[0072] Carbon nanotubes: diameter ≤15nm, length 5~15μm.
[0073] Graphene oxide: oxygen-carbon molar ratio is 0.45-0.65, sheet diameter is 15-50 μm, and sheet thickness is ≤10 nm.
[0074] Animal protein foaming agent: FP-50A animal protein foaming agent purchased from Liaocheng Jiukun Building Materials Co., Ltd.
[0075] Examples 1 to 4 and Comparative Examples 1 to 6
[0076] LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2 (if any) and carbon nanotubes are added to 100 mL of 5 mg / mL graphene oxide dispersion, and ultrasonically dispersed uniformly; then 1 g of sodium ascorbate and 0.25 g of animal protein foaming agent are added, and stirred at 12000 rpm until the foam is uniform to obtain a foam. The foam is kept at 95°C for 6 hours to form a wet gel. The wet gel is frozen at -20°C for 10 hours, and then thawed to obtain a dry gel.
[0077] The dried gel was washed with deionized water and ethanol, and then dried at 95°C; the upper and lower surfaces of the washed dried gel were cut off, and then pressed into sheets under 10 MPa to obtain a positive electrode aerogel material.
[0078] LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 The dosage of O2, carbon nanotubes and animal protein foaming agent is shown in Table 1.
[0079] Table 1
[0080]
[0081] Note: “—” means the raw material is not used.
[0082] Examples 5 to 8 and Comparative Examples 7 to 12
[0083] The positive electrode aerogel material is laminated to the aluminum mesh, then pressed at 20 MPa and cut to form the positive electrode.
[0084] The positive electrode is composed of a positive electrode current collecting layer formed by an aluminum mesh and a positive electrode active material layer formed by a positive electrode aerogel material; the thickness of the positive electrode current collecting layer is 12 μm, and the thickness of the positive electrode active material layer is 80 μm.
[0085] The selection of positive electrode aerogel materials is shown in Table 2.
[0086] Table 2
[0087]
[0088] Comparative Example 13
[0089] 15g LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, 1g polyvinylidene fluoride, and 1g carbon nanotubes were mixed evenly, and then slurried with N-methyl-2-pyrrolidone to obtain a slurry. The slurry was coated on an aluminum mesh, and then dried, rolled, cut into pieces, and vacuum dried to make a positive electrode.
[0090] The positive electrode is composed of a positive electrode current collecting layer formed by an aluminum mesh and a LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 The positive electrode active material layer is composed of O2 and carbon nanotubes; the thickness of the positive electrode current collecting layer is 12μm, and the thickness of the positive electrode active material layer is 80μm.
[0091] Examples 9 to 12 and Comparative Examples 14 to 20
[0092] 10g of hard carbon, 5g of graphite, 1g of polyvinylidene fluoride and 1g of carbon nanotubes were mixed evenly, and then slurried with N-methyl-2-pyrrolidone to obtain a slurry. The slurry was coated on a copper mesh, and then dried, rolled, cut into pieces, and vacuum dried to make a negative electrode. The negative electrode consisted of a negative electrode current collecting layer formed by a copper mesh and a negative electrode active material layer containing hard carbon, graphite and carbon nanotubes; the thickness of the negative electrode current collecting layer was 8μm, and the thickness of the negative electrode active material layer was 80μm.
[0093] The positive electrode, polyethylene microporous membrane and negative electrode are stacked to make a battery cell; the positive and negative electrode ears of the battery cell are welded, and then the battery cell is encapsulated with an aluminum-plastic film; 1 mol / L electrolyte (the electrolyte is LiBF4, and the solvent is propylene carbonate and dimethyl carbonate with a mass ratio of 1:1) is injected to assemble it into a supercapacitor.
[0094] The supercapacitor was charged and discharged at 25°C to test the energy density and power density. The charging and discharging conditions were 5A charging to 4.2V, constant voltage for 30min, and 5A discharging to 2.8V.
[0095] The selection of positive electrode and the energy density and power density of supercapacitor are shown in Table 3.
[0096] Table 3
[0097]
[0098] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A method for preparing a positive electrode aerogel material, characterized in that: The steps include: Containing 3.5 to 20 parts by weight of LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, 0.2-1 parts by weight of carbon nanotubes, 0.2-0.8 parts by weight of graphene oxide, a reducing agent, 0.1-0.4 parts by weight of an animal protein foaming agent and water are formed into a dispersion, stirred and foamed to obtain a foam; The foam is kept warm at 70-120° C. to obtain a wet gel; the wet gel is frozen to obtain a positive electrode aerogel material.
2. The preparation method according to claim 1, characterized in that: The insulation time is 3 to 9 hours, and the freezing temperature is -30 to -5°C.
3. The preparation method according to claim 1, characterized in that: The dosage of the reducing agent is 0.2 to 2 parts by weight, and the reducing agent is ascorbate; in the dispersion, the concentration of graphene oxide is 3 to 9 mg / mL.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The following steps are also included: The dried gel obtained after freezing is washed and dried; and pressed into sheets under the condition of 5-20 MPa to obtain the positive electrode aerogel material.
5. A positive electrode aerogel material, characterized in that: The positive electrode aerogel material is prepared by the preparation method according to any one of claims 1 to 4.
6. A positive electrode, characterized in that The positive electrode comprises a positive electrode current collector layer and a positive electrode active material layer formed of the positive electrode aerogel material according to claim 5, and the positive electrode active material layer is attached to the surface of the positive electrode current collector layer.
7. The method for preparing a positive electrode according to claim 6, characterized in that: The steps include: The positive electrode aerogel material is laminated to the current collector and then pressed to obtain the positive electrode.
8. A supercapacitor, characterized in that: The supercapacitor comprises the positive electrode according to claim 6.
9. The supercapacitor according to claim 8, characterized in that: The supercapacitor also includes a negative electrode and an electrolyte; The negative electrode comprises a negative electrode current collector layer and a negative electrode active material layer, wherein the negative electrode active material layer is attached to the surface of the negative electrode current collector layer, and the negative electrode active material layer comprises hard carbon, graphite and carbon nanotubes in a mass ratio of (5-15):(1-10):1; The electrolyte comprises an electrolyte and a solvent, wherein the electrolyte is LiBF4, and the solvent is propylene carbonate and dimethyl carbonate in a mass ratio of 1:(0.5-3); the concentration of the electrolyte is 0.5-3 mol / L.
10. The supercapacitor according to claim 8 or 9, characterized in that: The supercapacitor comprises a packaging shell, a battery core and an electrolyte; the battery core and the electrolyte are located in the packaging shell; the battery core comprises a positive electrode, a diaphragm and a negative electrode, and the diaphragm is a polyethylene microporous film.
